PROFILE IN GANGLIOSIDE ANTIBODIES IN BENIGN PROSTATIC HYPERPLASIA - Ilinca Nicolae (Romanian Journal of Neurology, 2016)
Molecular pathology of benign prostatic hyperplasia is multifactorial and involves endocrine, biochemical, immunological interactions. The mechanisms involved in the onset and progression of benign prostatic hyperplasia are: infections, older than 50 years, imbalances in hormones and neurotransmitters, inflammation, oxidative stress. It is estimated that an infectious etiology can be a cause of wrong immune response directed at the prostate. Inflammatory neuropathies often occur after infections with various microorganisms. It is also known, that the presence of microorganisms is heterogeneous in patients with benign prostatic hyperplasia. In this paper we documented the antibody profile of anti-GM1, -GM2, -GM3, -GD1a, -GD1b, -GT1b, -GQ1b IgG and IgM type in 30 patients with benign prostatic hyperplasia and in 30 controls. The results showed an increasing anti-GD1a and anti-GQ1b titer in patients with benign prostatic hyperplasia compared to control. The authors suggest that a careful monitoring of the patients developing an endogenous anti-gangliosidic immune response is required in order to assess these antibodies as potential risk factors for neuropathy in patients with benign prostatic hyperplasia.